Continuity of Care (COC) pada Ny. B Umur 30 Tahun G2P1A0 di PMB X - Eva Desitasari; Windayanti, Hapsari (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of midwifery care from pregnancy, childbirth, postpartum, neonate until deciding to use family planning. This aims to help monitor and detect the possibility of complications that accompany the mother and baby from pregnancy until the mother uses family planning. The method of midwifery care at PMB X and through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.